Cinema insights: The power of movies for adult learners - Khalish, Fakhuriy Fieddienil; Hanami, Yuliana (ProTVF, 2025)
Background: Modern adults frequently integrate movie watching into their daily routines. While traditionally regarded as entertainment, movies have also been recognized as valuable learning and personal growth tools. While previous research has demonstrated the effectiveness of movies as educational tools in academic settings, there is a notable scarcity of studies focusing on their application among adults in Indonesia. Purpose: This study aimed to discover the utilization of movies as a learning tool for adults. We explored all types of lessons adults learn after they watch movies and examined how movies reflect their problems. Methods: A qualitative descriptive approach was employed, involving seven participants selected through snowball sampling. Data collection was conducted using an online questionnaire with open-ended questions. Thematic analysis was applied to analyze the data. Results: Three prominent themes emerged from the data processing: (1) learning about various relationships, (2) the movie as a mirror of reality, and (3) key elements of a memorable movie for adults. The emerging themes aid us in gaining a deeper understanding of how adults perceive and derive meaning from the movies they watch. Conclusion: The findings indicated that movies offer adults meaningful insights. Moreover, watching movies contributed to their understanding of intrapersonal and interpersonal relationships. Additionally, movies serve as a stimulus for self-reflection. Therefore, these findings have implications for instructional designers who leverage movies as inspirational and educational tools. Implications: This study highlights that movies are more than just entertainment—they can inspire adults, specifically those aged 18-40. The insights gained from this research can be applied to adult learning experiences, particularly those incorporating movies as valuable educational tools.